Serine Hydroxymethyltransferase 1 Is Essential for Primary-Root Growth at Low-Sucrose Conditions - Yang Yuan (International Journal of Molecular Sciences, 2022)
Plant roots are essential organs for absorbing nutrients from the soil or medium. Sucrose functions as a vital carbon source in root development, and sucrose starvation interferes with the redox state of plant cells. However, the mechanism of root growth at sucrose starvation remains unclear. Here, we report that SHMT1 (serine hydroxymethyltransferase 1) plays a crucial role in primary-root growth. SHMT1 mutation caused decreased sugar levels, excessive H2O2 accumulation, and severe root-growth arrest at sucrose-free conditions, whereas plants with SHMT1 overexpression had increased sugar and decreased H2O2 levels, and longer primary roots. Sucrose supply fully restored root growth of shm1-2, but CO2 alone could not, and SHMT1 is much more stable in roots than shoots at sucrose conditions, suggesting that SHMT1 accumulation in roots is critical for sucrose accumulation and root growth. Further ROS scavenging by GSH application or ROS synthesis inhibition by apocynin application or RBOHD mutation reduced H2O2 levels and partially restored the root-growth arrest phenotype of shm1-2 at low-sucrose conditions, suggesting that SHMT1 modulates root growth via sucrose-mediated ROS accumulation. Our findings demonstrated the role of SHMT1 in primary-root growth by regulating sucrose accumulation and ROS homeostasis in roots.